Perjanjian Internasional Sebagai Sumber Hukum Internasional Dalam Praktik Hubungan Antar Negara - Mutiara Deja Saputri; Nabila Zahra Okta Dwiwani; Ema Septaria; M. Ilham Adepio (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study aims to analyze the legal arrangements of diplomatic immunity and examine the form of abuse of such immunity by diplomatic officials in the practice of international relations. In addition, this study also discusses the legal implications arising from the abuse of diplomatic immunity and efforts to counter it. The research method used is normative legal research with a legislative approach and a conceptual approach, supported by literature studies through various primary and secondary legal sources. The results of the study show that diplomatic immunity as stipulated in the Vienna Convention on Diplomatic Relations of 1961 is a functional legal instrument to ensure the smooth implementation of diplomatic duties, not as an absolute right for diplomatic officials. However, in practice, there are still frequent abuses of diplomatic immunity in various forms, ranging from administrative violations, civil violations in commercial activities, to serious criminal acts. These abuses show that there is a gap between legal norms and their implementation in the field. The legal implications of the abuse of diplomatic immunity include the inhibition of law enforcement in the recipient country, the emergence of potential impunity, and the disruption of diplomatic relations between countries. Therefore, countermeasures are needed through the optimization of diplomatic legal mechanisms, such as the implementation of persona non grata and waiver of diplomatic immunity, as well as strengthening supervision by sending countries and increasing international cooperation. Thus, it is hoped that a balance will be created between the protection of diplomatic functions and law enforcement in international relations.